2017
DOI: 10.3389/fmicb.2017.01226
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Novel Faecalibacterium prausnitzii Strains Isolated from Healthy Volunteers: A Step Forward in the Use of F. prausnitzii as a Next-Generation Probiotic

Abstract: Faecalibacterium prausnitzii is a major member of the Firmicutes phylum and one of the most abundant bacteria in the healthy human microbiota. F. prausnitzii depletion has been reported in several intestinal disorders, and more consistently in Crohn's disease (CD) patients. Despite its importance in human health, only few microbiological studies have been performed to isolate novel F. prausnitzii strains in order to better understand the biodiversity and physiological diversity of this beneficial commensal spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
224
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(259 citation statements)
references
References 49 publications
16
224
2
2
Order By: Relevance
“…Faecalibacterium prausnitzii ( F. prausnitzii ) are the predominant butyrate‐producing bacteria in the gastrointestinal tract. Studies have revealed that F. prausnitzii are critical in host health and in many diseases …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faecalibacterium prausnitzii ( F. prausnitzii ) are the predominant butyrate‐producing bacteria in the gastrointestinal tract. Studies have revealed that F. prausnitzii are critical in host health and in many diseases …”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that F. prausnitzii are critical in host health and in many diseases. [18][19][20] Metabolites from F. prausnitzii culture supernatant possess beneficial effects in inflammatory bowel disease (IBD). 21 Recently, a protein produced by F. prausnitzii called microbial anti-inflammatory molecule (MAM) was identified.…”
mentioning
confidence: 99%
“…The majority of bacteria from the Firmicutes phylum cannot utilise milk and mucin glycans (Lopez-Siles et al 2012, Marcobal et al 2010, Martin et al 2017, Sheridan et al 2016 except some strains of Ruminococcus gnavus and Ruminococcus torques (Crost et al 2013, Hoskins 1993. However, Lachnospiraceae and Ruminococcaceae are observed to be enriched at the mucosal environment suggesting metabolic interaction with the mucus-degrading species (Nava et al 2011, Van den Abbeele et al 2013.…”
Section: Comparative Genomics Reveal Thatmentioning
confidence: 99%
“…By analyzing the microbiome between healthy and diseased individuals, a variety of bacteria have been found to correlate with diseases . Meanwhile, some bacteria were found being more abundant in the healthy population and might have potential to be used as probiotics . These newly discovered bacteria, originated from the microbiome‐based analysis, could be referred to as the “next‐generation probiotics.” Indeed, the amelioration of culture system, including the development of bioreactors, formulation of new isolation protocol, and modification of culture media, also contribute to the discovery of next‐generation probiotics.…”
Section: Microbiome‐based Anti‐obesity Potential: Next‐generation Promentioning
confidence: 99%
“…Meanwhile, some bacteria were found being more abundant in the healthy population and might have potential to be used as probiotics . These newly discovered bacteria, originated from the microbiome‐based analysis, could be referred to as the “next‐generation probiotics.” Indeed, the amelioration of culture system, including the development of bioreactors, formulation of new isolation protocol, and modification of culture media, also contribute to the discovery of next‐generation probiotics. The development of metabolomics, an advanced technique for analyzing both the composition of metabolites from microbes and host, allows the researchers to establish the potential link between microbes and host, and provides the possible mechanisms for further investigation .…”
Section: Microbiome‐based Anti‐obesity Potential: Next‐generation Promentioning
confidence: 99%